2013
DOI: 10.1002/jat.2862
|View full text |Cite
|
Sign up to set email alerts
|

Rat pancreatitis produced by 13‐week administration of zinc oxide nanoparticles: biopersistence of nanoparticles and possible solutions

Abstract: Zinc oxide (ZnO) nanoparticles (NPs) are used in diverse applications ranging from paints and cosmetics to biomedicine and food. Although micron-sized ZnO is a traditional food supplement, ZnO NPs are an unknown public health risk because of their unique physicochemical properties. Herein, we studied the 13-week subchronic toxicity of ZnO NPs administered via the oral route according to Organization for Economic Cooperation and Development (OECD) test guideline 408. Well-dispersed ZnO NPs were administered to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
48
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 20 publications
(24 reference statements)
0
48
0
1
Order By: Relevance
“…This suggests that the highest dose administered remained in the blood circulation 24 hours after final gavage. The no observed adverse-effect level of ZnO nanoparticles was 268.4 mg/kg for both male and female rats, 27 which seems to be closely correlated to persistence at 536.8 mg/kg in the body. Similar observations were found in a repeated dose 90-day oral TK study of 20 nm ZnO nanoparticles suspended in citrate/HEPES in rats;…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…This suggests that the highest dose administered remained in the blood circulation 24 hours after final gavage. The no observed adverse-effect level of ZnO nanoparticles was 268.4 mg/kg for both male and female rats, 27 which seems to be closely correlated to persistence at 536.8 mg/kg in the body. Similar observations were found in a repeated dose 90-day oral TK study of 20 nm ZnO nanoparticles suspended in citrate/HEPES in rats;…”
mentioning
confidence: 78%
“…21 The conclusion was drawn that the absorption of zinc ions from ZnO nanoparticles under acidic gastric conditions contributes to their oral toxicity -pancreatitis. 27 Paek et al recently demonstrated a contradicting report of partial dissolution (13%-14%) of 20 and 70 nm ZnO nanoparticles capped with citrate/HEPES or l-serine/HEPES in simulated gastric fluid. 26 When absorbed plasma levels and tissue-distribution concentration of ZnO nanoparticles or ZnCl 2 were calculated based on soluble …”
Section: Biological Fatementioning
confidence: 99%
“…A previous 90-day toxicity study of ZnO NPs reported that the manufactured NPs induced lesions attributable to pancreatitis. 23 Similarly, another study showed that the 14-day oral administration of 20 nm ZnO NPs in mice induced mild infiltration of inflammatory cells in the liver and pancreas, with severe stomach mucosal damage. 24 In addition, the oral administration of 20 nm ZnO NPs and ZnO microparticles in SD rats provoked histological lesions in the liver, pancreas, heart, and stomach.…”
mentioning
confidence: 96%
“…Similarly, 13-week oral administration of 40 nm ZnO NPs in SD rats induced significant changes in anemia-related parameters such as Hb levels, Ht levels, MCV, and MCH. 21 Overdosing of metallic zinc…”
mentioning
confidence: 99%